2003
DOI: 10.2224/sbp.2003.31.6.603
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Changes in Female Sexual Desire: A Review

Abstract: The recognition that sexual desire is associated with relationship quality and other important interpersonal experiences has led to a corresponding interest in identifying the correlates and causes of this aspect of human sexual response. Most researchers have focused on intraindividual factors, including hormonal processes. The present review explores the relationship between one hormonally mediated female life event -pregnancy -and sexual desire. Sexual desire is defined and distinguished from other sexual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
1
8
0
4
Order By: Relevance
“…Consistent with previous findings (Regan et al 2003), the desire for another child (as reported by both partners) shortens the time since last coitus and diminishes the odds of contraceptive use among concordant couples.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous findings (Regan et al 2003), the desire for another child (as reported by both partners) shortens the time since last coitus and diminishes the odds of contraceptive use among concordant couples.…”
Section: Discussionsupporting
confidence: 89%
“…Das Interesse an Sexualität und die Häufigkeit von Sexualkontakten verändern sich im Verlaufe der Schwangerschaft (Dreyer 1993;Regan et al 2003;von Sydow 1999von Sydow , 2006Ahrendt et al 1995;Ahrendt u. Friedrich 2010). Diese Veränderungen können beziehungsfestigend, aber auch -trennend wirken.…”
Section: Schwangerschaft Und Sexualitätunclassified
“…For example, sexual desire is a psychological and mental experience (personally) that is generally known as stretching towards sexual goals or sexual function. Although desire, arousal, and sexual activity can often occur simultaneously, they alone cannot constitute the characteristics required for sexual desire [2]. "The passion for proximity is not only physical, but also psychological, and manifests itself in a succession of special pleasures for privacy with the beloved," and the quality of sexual and romantic satisfaction in healthy people evolves over time and Enhanced by acquaintance and intimacy.…”
Section: Introductionmentioning
confidence: 99%